2011
DOI: 10.1083/jcb.2011031321941c
|View full text |Cite
|
Sign up to set email alerts
|

Cbp3–Cbp6 interacts with the yeast mitochondrial ribosomal tunnel exit and promotes cytochrome b synthesis and assembly

Abstract: The authors have noted an error to a sentence in the abstract. The correct sentence appears below.The html and pdf versions of this article were corrected on June 20, 2011. The error remains only in the print version.On the one hand, the interaction of Cbp3 and Cbp6 with mitochondrial ribosomes is necessary for efficient translation of cytochrome b transcript. JCB: Correction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Indeed, the binding of Cbp3 along with Cbp6 to cytochrome b is important to protect the newly synthesized polypeptide from proteolytic degradation and to promote its insertion into the inner mitochondrial membrane. This assembly step does possibly require Cbp4 factor that mediates the assembly of cytochrome b into a functional bc 1 complex [14]. The two-dimensional analysis of the ΔCOR1/ΔCOR2 deletion strain expressing Cor2-TAP showed a co-migration of the bc 1 early core and Cbp3 and Cbp4 (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, the binding of Cbp3 along with Cbp6 to cytochrome b is important to protect the newly synthesized polypeptide from proteolytic degradation and to promote its insertion into the inner mitochondrial membrane. This assembly step does possibly require Cbp4 factor that mediates the assembly of cytochrome b into a functional bc 1 complex [14]. The two-dimensional analysis of the ΔCOR1/ΔCOR2 deletion strain expressing Cor2-TAP showed a co-migration of the bc 1 early core and Cbp3 and Cbp4 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…4), according to their function in Cyt b maturation [12][13][14][15]. Indeed, the binding of Cbp3 along with Cbp6 to cytochrome b is important to protect the newly synthesized polypeptide from proteolytic degradation and to promote its insertion into the inner mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibody against protein A was obtained from Sigma. Isolation of mitochondria, northern blotting (Gruschke et al, 2011), step-gradient purification of isolated mitochondria (Meisinger et al, 2000), and quantitative mass spectrometry were performed as described. …”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…Recent work has demonstrated that translational activators coordinate mitochondrial and nuclear gene expression to facilitate biogenesis of the OXPHOS (Gruschke et al, 2012;Mick et al, 2011). In the case of cytochrome b biogenesis, this feedback loop involves binding of a translational activator complex to the ribosomal tunnel exit to enable efficient interaction of the newly synthesized protein with an assembly factor (Gruschke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%